2020
DOI: 10.1002/jmv.25915
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system involvement by severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2)

Abstract: Neurologic sequelae can be devastating complications of respiratory viral infections.We report the presence of virus in neural and capillary endothelial cells in frontal lobe tissue obtained at postmortem examination from a patient infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Our observations of virus in neural tissue, in conjunction with clinical correlates of worsening neurologic symptoms, pave the way to a closer understanding of the pathogenic mechanisms underlying central ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
919
2
54

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 876 publications
(1,006 citation statements)
references
References 19 publications
31
919
2
54
Order By: Relevance
“…They concluded that there was an active viral entry across the brain microvasculature into the neurons, as there was blebbing of viral particles coming in and out of the endothelial membrane. [35] Mechanistically, SARS-CoV2 virus may enter the CNS through hematogenous route or retrograde synaptic transmission. ACE 2 receptors, which are abundantly expressed in the endothelial cells, supporting glia and neurons, might be the binding site facilitating hematogenous entry.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that there was an active viral entry across the brain microvasculature into the neurons, as there was blebbing of viral particles coming in and out of the endothelial membrane. [35] Mechanistically, SARS-CoV2 virus may enter the CNS through hematogenous route or retrograde synaptic transmission. ACE 2 receptors, which are abundantly expressed in the endothelial cells, supporting glia and neurons, might be the binding site facilitating hematogenous entry.…”
Section: Discussionmentioning
confidence: 99%
“…This expression suggests that SARS-CoV-2 could encounter its key binding target in the cerebrovasculature. Interestingly in Bryce et al, virus like particles were readily detectable by electron microscopy in the frontal lobe endothelium of a COVID-19 patient 38 .…”
Section: Whether Ace2 Expression Changes In Patients With Comorbiditimentioning
confidence: 94%
“…Additionally, many COVID-19 patients with severe disease do not respond well to artificial ventilation or display "silent hypoxia" (3), suggesting an extrapulmonary component to respiratory dysfunction, and cardiorespiratory function and fluid homeostasis are themselves subject to central nervous system (CNS) control. However, despite emerging reports of the post-mortem detection of the virus in the cerebrospinal fluid (CSF) (see for example (4)) or brain parenchyma of patients (5), little is known about how and under what circumstances SARS-CoV-2 infects the brain.…”
Section: Main Textmentioning
confidence: 99%